"We'll check vital signs only till we finish the school": experiences of student nurses regarding intra-semester clinical placement in Ghana - Charles Ampong Adjei; Collins Sarpong; Priscilla Adumoah Attafuah; Ninon P. Amertil; Yaw Abayie Akosah (BMC, 2018)
Abstract Background Clinical practicum is an integral part of nursing education because it provides students with opportunities to perform nursing care and practice specific nursing tasks. In Ghana, little is known about the experiences of baccalaureate student nurses with regard to intra-semester clinical practicum. This study therefore, explored perceptions, challenges, and how the intra-semester clinical practicum affects the learning process of student nurses in a private university in Ghana. Methods Exploratory descriptive phenomenological design was used. Nine in-depth interviews and three focus group discussions were conducted for baccalaureate student nurses in their second, third and fourth years of study. Only those who have attended intra-semester clinical practicum for at least two semesters in the course of their study were recruited. Purposive sampling technique was used to select the participants. The sample size was based on data saturation, however, a total of 33 participants were recruited. Data was analysed using content analysis technique. Results The findings show that baccalaureate student nurses perceive the intra-semester clinical practicum as beneficial. It affords the opportunity to translate theoretical knowledge into practice concurrently. However, students recounted their stressful experiences during the clinical period which negatively affected their academic work. Additionally, staff nurses assigned the students to do menial jobs instead of appropriate nursing tasks. Conclusions A review of the "block" method in which students will go to clinicals for a stipulated number of consecutive days in a month and then resume lectures, is worth considering.